2004
DOI: 10.1002/j.1556-6678.2004.tb00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Self Mediates College Stress and Adjustment

Abstract: Differentiation of self involves the capacity to modulate affect, maintain a clear sense of self, and balance intimacy and autonomy in significant relationships. Given the central role of family relationships for individual functioning, the authors tested whether differentiation mediated or moderated relations between college stress and personal adjustment. Differentiation of self partially mediated effects of academic and financial stress and exerted a direct influence on adjustment. Limitations, directions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
102
0
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 43 publications
12
102
0
9
Order By: Relevance
“…Studies have also shown that higher levels of differentiation of self are linked to greater marital satisfaction among heterosexual and same-sex couples (e.g., Kosek, 1998;Montes-Berges, 2009;Parsons, Nalbone, Killmer &Wetchler, 2007;Peleg, 2008;Skowron, 2000;Spencer & Brown, 2007), and adults who report greater differentiation of self are at lower risk for engaging in child abuse and other forms of family violence (Skowron, Kozlowski, & Pincus, 2010;Skowron & Platt, 2005). Also, findings indicate that differentiation appears to moderate (Knauth, Skowron & Escobar, 2006;Murdock & Gore, 2004) and mediate (Skowron Wester & Azen, 2004), the effects of stress on coping and adjustment in emerging adults. Research investigating the impact of differentiation of self on health-related behavior suggests it may enhance physical health functioning (e.g., Murray, Murray & Daniels, 2007;Peleg, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Studies have also shown that higher levels of differentiation of self are linked to greater marital satisfaction among heterosexual and same-sex couples (e.g., Kosek, 1998;Montes-Berges, 2009;Parsons, Nalbone, Killmer &Wetchler, 2007;Peleg, 2008;Skowron, 2000;Spencer & Brown, 2007), and adults who report greater differentiation of self are at lower risk for engaging in child abuse and other forms of family violence (Skowron, Kozlowski, & Pincus, 2010;Skowron & Platt, 2005). Also, findings indicate that differentiation appears to moderate (Knauth, Skowron & Escobar, 2006;Murdock & Gore, 2004) and mediate (Skowron Wester & Azen, 2004), the effects of stress on coping and adjustment in emerging adults. Research investigating the impact of differentiation of self on health-related behavior suggests it may enhance physical health functioning (e.g., Murray, Murray & Daniels, 2007;Peleg, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…High achievers in a highly competitive academic environment tend to focus on achievement through competing and comparing (18) , and they are more likely to face pressure from examination or relationship problems. Academic issues (19) , family problems (20) , peer rejection (21) , and personal distress (22) affect all adolescents regardless of academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Construct validity is indicated by relationship found between DSI scores and less symptomatology as well as less chronic anxiety (Skowron & Friedlander, 1998). In a study examining the relationship between differentiation of self and psychological adjustment, Skowron, Wester, and Azen (2004) also found that DSI-R correlated (r = .61) with psychological functioning, evidencing construct validity.…”
Section: Differentiation Of Selfmentioning
confidence: 97%